2022
DOI: 10.30762/jeels.v5i2.80
|View full text |Cite
|
Sign up to set email alerts
|

English Teaching in Vocational High School: A Need Analysis

Abstract: This research investigates the vocational school students’ needs on the implementation of English teaching and learning that is focused on the target needs and learning needs. By adapting Hutchinson and Waters’ model (1987), questionnaire consisting of parts A and B was administered to 32 students. Part A deals with the target needs centred on the learner’s necessities, lacks and wants that are effectively functioned in the target situation. In contrast, part B concerns about learning needs that encompass lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…It is difficult to find an appropriate material which answers the needs of the teacher, students, and curriculum. Mahbub (2019) has found that in the context of vocational education in Indonesia, the fact revealed that both school-based curriculum (KTSP) and the curriculum 2013 (K13) of VHS and general schools have the same English learning materials. More surprisingly, the English teachers in both VHS and general schools even use the same course books that are provided by markets that the contents are frequently inadequate to the VHS students' needs.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to find an appropriate material which answers the needs of the teacher, students, and curriculum. Mahbub (2019) has found that in the context of vocational education in Indonesia, the fact revealed that both school-based curriculum (KTSP) and the curriculum 2013 (K13) of VHS and general schools have the same English learning materials. More surprisingly, the English teachers in both VHS and general schools even use the same course books that are provided by markets that the contents are frequently inadequate to the VHS students' needs.…”
Section: Introductionmentioning
confidence: 99%
“…Article 1(3) of Chapter I of Government Regulation No. 29 of 1990 on Secondary Education in the Republic of Indonesia suggests that vocational education needs to center on the cultivation of students' expertise in certain disciplines (Mahbub, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…From these various studies, it can be concluded that all efforts to plan and develop the learning, including the development of questions, must begin with a needs analysis. The results of the needs analysis reveal the main considerations to be made to meet the needs of students and teachers (Mahbub, 2018;Ratri & Puspitasari, 2019;Onas, Nurhayati, & Mukmin, 2022;Vongvilay, Kartika, & Laila, 2020;Yundayani, Emzir, & Rafli, 2017). Similarly, the needs analysis can also identify the problems occurring to the students and teachers, knowledge or skills, expectations and media that are desired in the learning process.…”
Section: Introductionmentioning
confidence: 99%